2006
DOI: 10.1111/j.1365-3040.2005.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of different aldehyde dehydrogenase genes in Arabidopsis thaliana confers tolerance to abiotic stress and protects plants against lipid peroxidation and oxidative stress

Abstract: Aldehyde dehydrogenases (ALDHs) play a major role in the detoxification processes of aldehydes generated in plants when exposed to abiotic stress. In previous studies, we have shown that the Arabidopsis thaliana ALDH3I1 gene is transcriptionally activated by abiotic stress, and over-expression of the ALDH3I1 gene confers stress tolerance in transgenic plants. The A. thaliana genome contains 14 ALDH genes expressed in different sub-cellular compartments and are presumably involved in different reactions. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
248
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 315 publications
(269 citation statements)
references
References 59 publications
10
248
0
2
Order By: Relevance
“…Reliable controls include observations in the wild type and YFP alone transgenic plants that argue against other possibilities of the predicted subcellular localizations. To our knowledge, characterized plant ALDHs have been demonstrated to be targeted to diverse compartments including mitochondria (Busch and Fromm 1999;Nakazono et al 2000;Deuschle et al 2001;Liu et al 2001;Skibbe et al 2002), plastid/chloroplast (Kirch et al 2001;Weigel et al 1986;Kotchoni et al 2006), Cytosol (Rumpho et al 1983Nair et al 2004;Kotchoni et al 2006), and peroxisome (Nakamura et al 1997). Although the biochemical function of the aldehyde dehydrogenase characterized here is not yet clear, physiological properties suggest a detoxification function in plastids.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Reliable controls include observations in the wild type and YFP alone transgenic plants that argue against other possibilities of the predicted subcellular localizations. To our knowledge, characterized plant ALDHs have been demonstrated to be targeted to diverse compartments including mitochondria (Busch and Fromm 1999;Nakazono et al 2000;Deuschle et al 2001;Liu et al 2001;Skibbe et al 2002), plastid/chloroplast (Kirch et al 2001;Weigel et al 1986;Kotchoni et al 2006), Cytosol (Rumpho et al 1983Nair et al 2004;Kotchoni et al 2006), and peroxisome (Nakamura et al 1997). Although the biochemical function of the aldehyde dehydrogenase characterized here is not yet clear, physiological properties suggest a detoxification function in plastids.…”
Section: Discussionmentioning
confidence: 78%
“…The levels of lipid peroxidation in plant cells were assayed with the thiobarbituric acid test, which determines the amounts of MDA as end product of lipid peroxidation (Heath and Packer 1968;Loreto and Velikova 2001;Sunkar et al 2003). A recent study also demonstrated that the reduced levels of MDA accumulation were correlated with the elevated stress tolerance in the transgenic overexpressors of several Arabidopsis ALDH genes (Kotchoni et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports suggested that Gm TP55 from G. max and ALDH7B4 from A. thaliana might be involved in the detoxification of reactive aldehyde species generated by oxidative stress-associated lipid peroxidation (Kirch et al 2005;Kotchoni et al 2006;Rodrigues et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the ALDH7B6 gene from the moss T. ruralis is constitutively expressed in response to osmotic stress and ABA (Chen et al 2002). But recent study suggested that the Gm TP55 gene from G. max might be involved in the detoxification of reactive aldehyde species generated by oxidative stress-associated lipid peroxidation (Rodrigues et al 2006) and ALDH7B4 from A. thaliana not only function as aldehyde detoxifying enzymes, but also as efficient reactive oxygen species scavengers and lipid peroxidation-inhibiting enzymes (Kirch et al 2005, Kotchoni et al 2006. However, the exact physiological functions of members of the ALDH7 family remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%